2016
DOI: 10.5194/hess-20-1049-2016
|View full text |Cite
|
Sign up to set email alerts
|

Fault damage zone volume and initial salinity distribution determine intensity of shallow aquifer salinisation in subsurface storage

Abstract: Abstract. Injection of fluids into deep saline aquifers causes a pore pressure increase in the storage formation, and thus displacement of resident brine. Via hydraulically conductive faults, brine may migrate upwards into shallower aquifers and lead to unwanted salinisation of potable groundwater resources. In the present study, we investigated different scenarios for a potential storage site in the Northeast German Basin using a three-dimensional (3-D) regional-scale model that includes four major fault zone… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
5
11
0
Order By: Relevance
“…The latter implies the need to have good knowledge of the a priori salt distribution. This is in good qualitative agreement with findings by (Tillner et al, , 2016, , and (Walter et al, 2013). The results also imply that it is unlikely to observe sudden and strong increases in the salt concentration due to CO 2 injection at locations where elevated concentrations have not been an issue before.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The latter implies the need to have good knowledge of the a priori salt distribution. This is in good qualitative agreement with findings by (Tillner et al, , 2016, , and (Walter et al, 2013). The results also imply that it is unlikely to observe sudden and strong increases in the salt concentration due to CO 2 injection at locations where elevated concentrations have not been an issue before.…”
Section: Discussionsupporting
confidence: 81%
“…Kissinger et al: Part 2: A simulated case study in the North German Basin 2753 ary conditions and hydrogeological parameterization but also with respect to the initial salt concentration in the system. (Tillner et al, 2016) confirmed this finding, while additionally stressing the importance of the fault-damage-zone volume determining the intensity of the salinization of shallow freshwater aquifers.…”
Section: Introductionsupporting
confidence: 75%
“…Therefore, the calculation of salt transport into shallow aquifers is not only uncertain with respect to the boundary conditions and hydrogeological parametrization but also with respect to the initial salt concentration in the system. Tillner et al (2016) confirm this finding, while additionally stressing the importance of the fault-damage-zone volume determining the intensity of the salinization of shallow freshwater aquifers.…”
Section: Introductionsupporting
confidence: 72%
“…The risks include gas losses, contaminant migration and uncontrolled water influx [3]. However, recent numerical simulations on fault reactivation are mainly associated to hydraulic fracturing [67], CO 2 storage [68,69] and geothermal heat recovery [70], whereas the process of fault reactivation was not yet adequately represented in the field of underground coal gasification [27].…”
Section: Discussionmentioning
confidence: 99%